Government of Madhya Pradesh Draft Annual Plan 1979-80 Supplementary Note Roads and Bridges - Government of Madhya Pradesh (Government of Madhya Pradesh, 1978)
The Government of Madhya Pradesh’s Draft Annual Plan 1979-80 highlights the status and proposals for roads and bridges under the Fifth and Sixth Five Year Plans, focusing on rural connectivity and the Minimum Needs Programme (MNP). During the Fifth Plan (1974-78), 1,341 unconnected villages with populations of 1,500 and above were targeted for pucca road connectivity, alongside 1,100 other road projects totaling 20,000 km and 78 major bridges, with an overall estimated cost of Rs. 122.29 crores. However, due to Planning Commission ceilings and limited outlays (Rs. 37.50 crores), the programme was curtailed, achieving 3,469 km of pucca roads connecting 390 villages with populations above 2,500 and 1,851 villages below 1,500. The Sixth Plan (1978-83) proposes linking all remaining villages with populations of 1,500 and above, and half of those with 1,000–1,499 population, with a total outlay of Rs. 115 crores for new works, plus Rs. 31.28 crores for carry-over roads, totaling Rs. 146 crores. The plan emphasizes cost-effective construction with Part I and Part II classification, cross drainage provisions, and year-wise outlay allocation to maximize rural benefits. Special attention is given to tribal areas, covering 37.8% of the State, where average road density is only 8.3 km per 100 sq. km, below the national average of 16.5 km. Linking 415 remaining Market/Growth Centres is prioritized to uplift tribal populations. Supplementary assistance under the Food-for-Work and Advance Plan programmes was utilized to construct and maintain roads affected by drought and hailstorms, adding 50–75 km to plan roads and 150–170 km to link and crash roads annually. Overall, the plan underscores the critical need for enhanced rural road connectivity to promote socio-economic development, especially in underserved tribal regions.
Government of Madhya Pradesh
Government of Madhya Pradesh
Keywords: State Plan; Minimum Needs Programme; Madhya Pradesh; Village Connectivity; Pucca Roads; Rural Roads; Tribal Areas; Market/Growth Centres; Road Construction; Food-for-Work; Advance Plan Assistance